(untitled) (Praxis Educativa, 2022)
This research was carried out within the framework of the authors’ undergraduate studies, pursuing the objective of investigating the social representation of young people in school in relation to their insertion into the labor market in Río Cuarto (Córdoba) in 2019. In methodological matters, it is a qualitative study of an exploratory-descriptive type, driven by the purpose of recognizing the characteristics of the social representations that the students of the city have about their future processes of insertion into the world of work, emphasizing in their perceptions about the link between their studies and the expectations and assessments of the local labor market. From a cross-sectional research design that draws on a primary source of data, under the technique of in-depth interviews, conducted with students in the last year of compulsory schooling, belonging to a publicly managed educational institution and another privately managed.